Islam and Islamic studies resources : for studying Islam and the diverse perspectives of Muslims - University of Georgia - Department of Philosophy and Religion (2008)
[Dt.:] Die Website 'Islam and Islamic studies' stellt ein Informationsportal dar, welches sich mit der Islamwissenschaft mit seinen unzähligen Subthemen wie der Koran, der Hadith, die Sunna, die Shia, Sufismus. Aktuelle Themen wie militanter Islam, Jihad, islamistischer oder muslmischer Extremismus, Terrorismus, Islam im Irak werden genauso vorgestellt wie klassische Themen wie muslimische Frauen, islamische Kunst, Architektur, Musik, Geschichte des Islams, islamische Theologie und Philosophie und Sprachen wie Arabisch oder Persisch. Erreicht werden sollen Interessenten für dieses Gebietes, die auf der einen Seite eine neutrale Perspektive des Islams bekommen sollen, aber auch diverse Sichtweisen von Muslimen wie z.B. aus den Gruppen der Sunniten, Shiiten, des Sufismus oder weitere. - [Engl.:] This website 'Islam and Islamic Studies' demonstrates a information-platform, which deals with islamic studies and its countless sub-topics such as the quran, the hadith, the sunnah, the shia and sufismus. Topicals as militant islam, jihad, islamistic or muslim extremism, terrorism, islam in iraq are being presented as well as classical fields like muslim women, islamic art, architecture and music, history of islam, islamic theology and philosophy and languages as arabic or persian. Aim should be to reach interested parties for this field, who, on the one hand should get a neutral sight of islam but on the other hand should also be able to see diverse perspectives of muslims as e.g. of groups like sunni islam, shiism, sufism or others.